Anti-aging effect of the combination of Bifidobacterium longum and B. animalis in a d-galactose-treated mice. (June 2020) - Xia, Chaofei; Cao, Xinyi; Cui, Lanyue; Liu, Hui; Wang, Shuai; Chen, Tingtao
Graphical abstract: Highlights: Probiotics are isolated from the faeces of centenarians in Bama longevity village Guangxi, China, attenuated d -gal-induced anxiety-like behaviour, uncoordinated movement and cognitive decline. Probiotics reduced the NF-κB/TLR4 induced-neuroinflammation and oxidative stress, ultimately protecting the d -gal-induced aging mice from cognitive decline. Probiotics improved the expression of Sirt 1, which could resist NF-κB/TLR4-induced -neuroinflammation and oxidative stress in d -gal-treated aging mice. Abstract: The protective effect of probiotics Bifidobacterium longu m, B. animalis and their combination on age-related cognitive decline is studied in the present work. We developed d -galactose (gal) (150 mg/kg/d)-treated mice, and oral administration of B. longum, B. animalis and their combination for 12 weeks. The results showed that these probiotics revered d -gal-induced anxiety-like behaviour, uncoordinated movement, cognitive decline, and hippocampus senescence. These probiotics also reduced the hippocampal mRNA expressions of interleukin (IL)-1β, IL-6, tumour necrosis factor (TNF)-α, malondialdehyde (MDA) activity, and increased the activities of glutathione peroxidase (GSH-PX) and superoxide dismutase (SOD). Additionally, the activation of toll-like receptor 4 (TLR4), nuclear-factor-κB (NF-κB) and downregulation of sirtuin 1 (Sirt 1) proteins was restored by probiotics treatment. Based on the results, we concluded that B. longum, B. animalis and their combination might ameliorate age-related cognitive deficits in d -gal-treated mice, potentially by inhibiting NF-κB/TLR4 induced-neuroinflammation and oxidative stress through up-regulating the expression of Sirt 1.